Design and Implementation of Low Profile Antenna for Dual-Band Applications Using Rotated E-Shaped Conductor-Backed Plane - Mahdi Jalali; Tohid Sedghi; Shahin Shafei (The Scientific World Journal)
A novel configuration of a printed monopole antenna with a very compact size for satisfying WLAN operations at the 5.2/5.8 GHz and also for X-band operations at the 10 GHz has been proposed. The antenna includes a simple square-shaped patch as the radiator, the rotated U-shaped conductor back plane element with embedded strip on it, and the partial rectangular ground surface. By using the rotated U-shaped conductor-backed plane with proper values, good impedance matching and improvement in bandwidth can be achieved, at the lower and upper bands. The impedance bandwidth for S11<-10 dB is about 1.15 GHz for 5 GHz band and 5.3 GHz for X-band. The measured peak gains are about 1.9 dBi at WLAN-band and 4.2 dBi at X-band. The experimental results represent that the realized antenna with good omnidirectional radiation characteristics, enough impedance bandwidth, and reasonable gains can be appropriate for various applications of the future developed technologies and handheld devices.